Hydroporator: a hydrodynamic cell membrane perforator for high-throughput vector-free nanomaterial intracellular delivery and DNA origami biostability evaluation. Issue 10 (9th April 2019) - Kizer, Megan E.; Deng, Yanxiang; Kang, GeoumYoung; Mikael, Paiyz E.; Wang, Xing; Chung, Aram J.
Abstract : We present a hydrodynamic cell deformation-induced intracellular delivery platform, termed "hydroporator". Abstract : The successful intracellular delivery of exogenous macromolecules is crucial for a variety of applications ranging from basic biology to the clinic. However, traditional intracellular delivery methods such as those relying on viral/non-viral nanocarriers or physical membrane disruptions suffer from low throughput, toxicity, and inconsistent delivery performance and are time-consuming and/or labor-intensive. In this study, we developed a single-step hydrodynamic cell deformation-induced intracellular delivery platform named "hydroporator" without the aid of vectors or a complicated/costly external apparatus. By utilizing only fluid inertia, the platform focuses, guides, and stretches cells robustly without clogging. This rapid hydrodynamic cell deformation leads to both convective and diffusive delivery of external (macro)molecules into the cell through transient plasma membrane discontinuities. Using this hydroporation approach, highly efficient (∼90%), high-throughput (>1 600 000 cells per min), and rapid delivery (∼1 min) of different (macro)molecules into a wide range of cell types was achieved while maintaining high cell viability. Taking advantage of the ability of this platform to rapidly deliver large molecules, we also systematically investigated the temporal biostability of vanilla DNA origami nanostructures in living cells for the first time. Experiments using two DNA origami (tube- and donut-shaped) nanostructures revealed that these nanostructures can maintain their structural integrity in living cells for approximately 1 h after delivery, providing new opportunities for the rapid characterization of intracellular DNA biostability.